2000
DOI: 10.1097/00005537-200011000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Expression of Aquaporin 2 in the Mouse Inner Ear

Abstract: Objectives:The maintenance of endolymph homeostasis is critical for the inner ear to perform its functions of hearing and maintaining balance. The identification and cloning of aquaporins (a family of water channel proteins) has allowed the study of a novel cellular mechanism potentially involved in endolymph homeostasis. The objective of the present study was to define the developmental temporal and spatial expression pattern of aquaporin 2 (Aqp2) in the developing mouse inner ear. Study Design: A systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…In sensory organs, AQP2 has been found in the developing (Merves et al, 2000) and adult (Mhatre et al, 2002) inner ear where it plays an important role in fluid homeostasis. We are not aware of any direct role played by vasopressin on the olfactory epithelia; however, this role, if any, should be limited to organogenesis and the early postnatal period because AQP2 in no longer found therein after P15.…”
Section: Aqpsmentioning
confidence: 99%
“…In sensory organs, AQP2 has been found in the developing (Merves et al, 2000) and adult (Mhatre et al, 2002) inner ear where it plays an important role in fluid homeostasis. We are not aware of any direct role played by vasopressin on the olfactory epithelia; however, this role, if any, should be limited to organogenesis and the early postnatal period because AQP2 in no longer found therein after P15.…”
Section: Aqpsmentioning
confidence: 99%
“…The localization of AQP2 protein is open to discussion. According to Merves et al [24] , immunohistochemical studies revealed that AQP2 protein is expressed in the cochlea and vestibular structure in the developing mouse inner ear. The endolymphatic duct and sac, and the stria vascularis expressions of AQP2 were noted to occur fairly late during development of the inner ear, but AQP2 protein was not histochemically detected near maturity.…”
Section: Hormonal Aspects Of MD On the Basis Of Experimental Studiesmentioning
confidence: 99%
“…Since the discovery of aquaporin (AQP) water channels (Agre et al, 1993), it has become clear that these channels play a crucial role in water homeostasis not only in the kidney but also in the inner ear. Indeed, expressions of proteins and/or mRNAs of AQPs in the inner ear have already been reported including negative reports (AQP-1: Stankovic et al, 1995;Sawada et al, 2003;AQP2: Kumagami et al, 1998;Beitz et al, 1999;Merves et al, 2000;Mhatre et al, 2002;Sawada et al, 2002;Fukushima et al, 2005;Zhong and Liu, 2003;AQP-3: Beitz et al, 1999;AQP-4: Takumi et al, 1998;Minami et al, 1998;AQP-5: Beitz et al, 1999;Mhatre et al, 1999;Löwenheim and Hirt, 2004;AQP-6: Fukushima et al, 2002;Lopez et al, 2007;Taguchi et al, 2008;AQP-7: Beitz et al, 1999;Huang et al, 2002;AQP-8: Beitz et al, 1999;Huang et al, 2002;and AQP-9: Huang et al, 2002). However, previous reports have had many contradictions.…”
Section: Introductionmentioning
confidence: 99%
“…Some data show that AQP-2 mRNA is present in rat cochlea (Mhatre et al, 2002;Sawada et al, 2002;Fukushima et al, 2004). In immunohistochemistry, Merves et al (2000) showed AQP-2 protein in the inner ear during mouse development, and Mhatre et al (2002) also showed not in the SV but in the structures bordering the cochlea of both rat and mouse including Reissner's membrane, the organ of Corti, inner and outer sulcus cells and the spiral limbus. However, other studies found AQP-2 protein only in Reissner's membrane (Zhong and Liu, 2003) or did not find it at all (Kumagami et al, 1998;Beitz et al, 1999).…”
Section: Introductionmentioning
confidence: 99%